Insensitivity of the distance ladder Hubble constant determination to Cepheid calibration modelling choices. Issue 4 (21st March 2018) - Follin, B; Knox, L
Abstract: Recent determination of the Hubble constant via Cepheid-calibrated supernovae by Riess et al.find ∼3σ tension with inferences based on cosmic microwave background (CMB) temperature and polarization measurements from Planck . This tension could be an indication of inadequacies in the concordance Λcold dark matter model. Here, we investigate the possibility that the discrepancy could instead be due to systematic bias or uncertainty in the Cepheid calibration step of the distance ladder measurement by Riess et al. We consider variations in total-to-selective extinction of Cepheid flux as a function of line of sight, hidden structure in the period–luminosity relationship, and potentially different intrinsic colour distributions of Cepheids as a function of host galaxy. Considering all potential sources of error, our final determination of H 0  = 73.3 ± 1.7 km s −1 Mpc −1 (not including systematic errors from the treatment of geometric distances or Type Ia supernovae) shows remarkable robustness and agreement with Riess et al. We conclude systematics from the modelling of Cepheid photometry, including Cepheid selection criteria, cannot explain the observed tension between Cepheid-variable and CMB-based inferences of the Hubble constant. Considering a 'model-independent' approach to relating Cepheids in galaxies with known distances to Cepheids in galaxies hosting a Type Ia supernova and finding agreement with the Riess et al. result, we conclude no generalization of the model relating anchor and host Cepheid magnitude measurements can introduce significant bias in the H 0 inference.